Discourse And Multimodal Analysis Of Musical Identity Construction On The Spout Podcast “LANY Breaks Down Their New Album, Paul Klein’s Car Accident, and What’s Next” - Virginia Larasati Putri Bayu; Eka Fadilah (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This study investigates how musical identity is constructed through discourse and multimodal communication in a podcast interview featuring Paul Jason Klein, the lead vocalist of LANY. The study aims to examine how Paul Klein employs Gee’s (2014) Seven Building Tasks of Language and how verbal and multimodal resources jointly contribute to the construction of his musical identity. A descriptive qualitative design was employed using the podcast episode LANY Breaks Down Their New Album, Paul Klein’s Car Accident, And What’s Next published on the Spout Podcast YouTube channel as the primary data source. The verbal data were analyzed using Gee’s Seven Building Tasks of Language, while multimodal elements, including facial expressions, gestures, eye contact, tone of voice, posture, and visual composition, were examined using Kress and van Leeuwen’s (2006) Multimodal Discourse Analysis. The interpretation of musical identity was guided by the framework proposed by MacDonald and Saarikallio (2022), consisting of Musical Journey, Values and Beliefs, Creative Process, Fan Relationship, and Digital Self-Presentation. The findings reveal that Paul Klein employs all seven Building Tasks of Language to communicate meanings, establish relationships, express artistic values, and construct his identity as an authentic musician. Moreover, discourse and multimodal resources function complementarily in representing his resilience, creativity, emotional openness, and close relationship with audiences. The study demonstrates that musical identity in digital media is constructed through the integration of linguistic and multimodal resources rather than through language alone.